2011
DOI: 10.1111/j.1365-4632.2011.05027.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of isotretinoin treatment on plasma holotranscobalamin, vitamin B12, folic acid, and homocysteine levels: non‐controlled study

Abstract: Isotretinoin (Iso) has been used for the treatment of acne. Some previous studies reported elevated homocysteine (Hcy) levels after treatment with Iso. Some side effects have clinical presentations similar to vitamin B12, folic acid deficiencies, and hyperhomocysteinemia. In the present study we evaluated the plasma Hcy levels, the vitamins involved in its metabolism (vitamin B12 and folic acid), and holotranscobalamin (HoloTC), a transport system for vitamin B12 absorption in patients receiving Iso treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 31 publications
(91 reference statements)
5
30
1
Order By: Relevance
“…It has been hypothesized that vitamin B 12 modulates the activities of the skin microbiota and contributes to AV pathogenesis [26]. On the other hand, reports have linked vitamin B 12 deficiency to the treatment of AV by isotretinoin [27]. In our data, there was no association between levels of vitamin B 12 and AV in univariable nor multivariable analysis.…”
Section: Discussioncontrasting
confidence: 74%
“…It has been hypothesized that vitamin B 12 modulates the activities of the skin microbiota and contributes to AV pathogenesis [26]. On the other hand, reports have linked vitamin B 12 deficiency to the treatment of AV by isotretinoin [27]. In our data, there was no association between levels of vitamin B 12 and AV in univariable nor multivariable analysis.…”
Section: Discussioncontrasting
confidence: 74%
“…Prolactin receptor (PRLR) was profoundly downregulated which is in line with a study in patients with acne where isotretinoin caused suppression of several pituitary hormones such as prolactin in patients' sera [58].…”
Section: Regulation Of Development Genes By Rasupporting
confidence: 83%
“…The current study was in continuation of several studies on the effect of isotritinoin on several biomarkers in the acne patients and found level of serum GGT, ALT, ALP , triglycerides, cholesterol , homocysteine were elevated after 3 months of the treatment and this results agree with other studies [Muhammad 2015, Polat 2008,, Vieira 2012,Fusun 2017, Hilal 2014 Although many studies reported alterations in serum transaminase and lipid levels, other studies reported no significant in the level of these parameters , such as Brito et al found no statistically significant changes in liver transaminase, TG levels following treatment withIsotretinoin.In another study by Javanbakht et al, serum levels of homocysteine was not elevated through treatment withIsotretinoin. The results showed a decrease in the serum level of folic acid , vitamin B 12 and vitamin B 7 after 3 months of treatment with Isotretinoin , this results in agreement with several studies [Muhammad 2015, Hilal 2014, Karadag 2011 , while disagrees withPolat 2008.…”
Section: Discussionsupporting
confidence: 90%